Implementation Babinkamtibmas Completion Of Problems In Regency - Antonius Iwan Murdianto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Bhabinkamtibmas is a member of the Police whose existence is closest to the people in each village / urban, so that its role is essential in creating security and public order. This study aims to assess and analyze the role of Bhabinkamtibmas in helping to resolve problems that occur in the region, the obstacles and overcoming these obstacles. The method used in this research is the socio-juridical. Sources and types of data using primary data and secondary data. Methods of data collection is done through field studies and literature, while the method of data analysis using qualitative analysis. The results showed that Bhabinkamtibmas role in helping to resolve problems that occur in the region is as a facilitator and mediator. As a facilitator, bhabinkamtibmas provide premises, facilities and infrastructures for the mediation process is usually done in the village hall, and as a mediator Bhabinkamtibmas lead the mediation process. Obstacles encountered Bhabinkamtibmas in helping to resolve problems that occur in the region is the presence of a third party to interfere in the settlement and lack of public awareness both of which were in conflict as well as the surrounding community. Efforts to overcome these obstacles is to conduct an intensive approach to the victim, the offender and his family.Keywords: Role; Bhabinkamtibmas; Problem Solving.